An economic analysis of bilateral investment treaties - Sasse, Jan Peter; SpringerLink (Online service). (Wiesbaden Gabler, 2011)
Bilateral Investment Treaties (BITs) are an important instrument for the protection of foreign direct investment (FDI). However, compared to international trade law, international investment law has so far received only little research attention from an economic point of view. By applying a law and economics approach, Jan Peter Sasse provides a systematic analysis of the way BITs function. He explains why BITs are more than just a signal, how they relate to institutional competition as well as to institutional quality and why transparency in international investment arbitration is hard to achieve and may even be detrimental.
International Investment Law and Expropriation Risk; Protection of Foreign Direct Investment through BITs; Institutional Competition and BITs; Transparency in Investment Arbitration
Electronic reproduction.
Keywords: Investments, Foreign; Investments, Foreign -- Law and legislation; Electronic books